Isolation and molecular characterization of porcine epidemic diarrhea viruses collected in Japan in 2014 - Horie, Masayuki; Kabemura, Mitsue; Masatani, Tatsunori; Matsuu, Aya; Ozawa, Makoto (Archives of virology, 2016)
Porcine epidemic diarrhea virus (PEDV) is the etiological agent of porcine epidemic diarrhea (PED), which is threatening the swine industry all over the world. In Japan, although there were no reported PED cases from 2007 to 2012, a large-scale PED outbreak started in 2013, causing severe economic losses. Although several PEDV studies have been conducted in Japan, more PEDV isolates and sequence information are needed to understand the molecular biology and epidemiology of PEDV. Here, we isolated seven Japanese PEDV strains from intestinal tissue samples collected in 2014 and determined the spike gene sequences of 13 Japanese PEDV strains, including the above seven isolates. Phylogenetic analysis shows that all of the strains are genetically distinct from classical Japanese PEDV strains isolated prior to 2013 and can be classified into two different genotypes: 12 strains belong to the North American clade composed of recent highly pathogenic PEDV strains, and the remaining one strain belongs to the so-called insertion deletion (INDEL) clade. These data suggest multiple PEDV invasions from abroad to Japan. Notably, compared to classical Japanese strains, all of the recent Japanese strains have two amino acid substitutions in a known neutralizing epitope. In addition, one of the strains acquired an additional mutation in another neutralizing epitope that is highly conserved among PEDVs, including the classical and recent isolates. Our isolates and findings will be useful for future investigations aimed at understanding, controlling, and preventing PED.